Egg hatching rates of brown-marbled grouper, Epinephelus fuscoguttatus under different light wavelengths and intensities - Mohammad Seth, Siti Nasihin; Nai, Han Tan; Rosli, Muhammad Khairulanwar; Saad, Shahbudin; Mohammad Noor, Normawaty; Mukai, Yukinori (Universiti Malaya, 2014)
This study was conducted to examine the egg hatching rates of brown-marbled grouper, Epinephelus fuscoguttatus under different light conditions in terms of light wavelengths and intensities. Results of two-way ANOVA showed significant difference for light wavelengths (p<0.05), while light intensities showed no significant difference. There was no interaction between light wavelengths and intensities. Post-hoc Tukey test showed that hatching rates under green light wavelength were significantly higher than white and yellow light wavelengths (p<0.05). When white light 2.7 μmoles/m²/s was set as the control, the hatching ratio of the brown-marbled grouper under green light 2.7 μmoles/m²/s was almost three times higher than the control. The lowest ratio of hatching rates was observed under the white light 13.3 μmoles/m²/s with 70 percent lower ratio of hatching rates than the control light. Eggs hatching under other light conditions mostly showed higher ratios than the control light.